2016
DOI: 10.1016/j.jamcollsurg.2016.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Patient Age on Outcomes in Breast Reconstruction: Results from a Multicenter Prospective Study

Abstract: Background Although over 40% of new breast cancer diagnoses in the U.S. are in older women, few studies have assessed the outcomes of post-mastectomy reconstruction in this population. Our objective was to evaluate age effects on postoperative complications and patient-report outcomes (PROs) in women undergoing breast reconstruction, and to investigate whether age effects differ between reconstructive procedure types. Study Design Eligible patients in the Mastectomy Reconstruction Outcomes Consortium study f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
58
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 29 publications
6
58
0
3
Order By: Relevance
“…11 However, there are also studies that report that increasing age in the setting of microvascular breast reconstruction did not lead to an increase in overall complications. 12,13,40 It is unclear why age was not a risk factor for overall complications in the larger two mastectomy weight cohorts. Regardless of mastectomy weight, there are demonstrated benefits for women undergoing reconstruction, most notably improved satisfaction with physical appearance and greater sexual well-being than younger women.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…11 However, there are also studies that report that increasing age in the setting of microvascular breast reconstruction did not lead to an increase in overall complications. 12,13,40 It is unclear why age was not a risk factor for overall complications in the larger two mastectomy weight cohorts. Regardless of mastectomy weight, there are demonstrated benefits for women undergoing reconstruction, most notably improved satisfaction with physical appearance and greater sexual well-being than younger women.…”
Section: Discussionmentioning
confidence: 99%
“…Butz et al found age to be a risk factor for VTE formation in the elderly undergoing autologous based reconstruction . However, there are also studies that report that increasing age in the setting of microvascular breast reconstruction did not lead to an increase in overall complications . It is unclear why age was not a risk factor for overall complications in the larger two mastectomy weight cohorts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In line with our results, Fisher et al, reported that advanced age not to be a predictor for complication rates after immediate breast reconstruction. More recently, Santosa et al prospectively analyzed complication rates in patients undergoing immediate vs delayed breast reconstruction with follow‐up period of 2 years. They grouped the patients into three groups: <45 years, 45‐60 years and >60 years of age, and found that increased age does not effect breast reconstruction complication.…”
Section: Discussionmentioning
confidence: 99%